Income inequality and happiness: Is there a relationship? - Paul Alois (Luxembourg Income Study (LIS), 2014)
This paper uses fixed effects regressions to examine the relationship between happiness and income inequality in 30 countries. It has three major findings. First, happiness and income inequality are correlated in the expected direction; high income inequality correlates with a smaller share of happy people and a higher share of unhappy people. Second, different regions have characteristics that strongly mediate the effect of income inequality on happiness. Third, the correlation between income inequality and happiness is of a similar magnitude to the correlation between median income and happiness.
Keywords: 330